Structure of the producing side of the wine industry: Firm typologies, networks of firms and clusters - Etienne Montaigne; Alfredo Manuel de Jesus Oliveira Coelho (Wine Economics and Policy, 2012)
The purpose of this article is to introduce what is traditionally known in France as the wine filière. The paper is divided into two parts. First, we will introduce the theoretical approaches and the main research questions relating to the 'filière analysis', by combining older references with the complementary approaches derived from more recent theoretical contributions. The filière analysis is based on three main historical theoretical streams and on four complementary and more recent approaches: the innovation chains, the global value chain (GVC), the theory of transaction costs and the marketing approach. In the second part of the paper, we will provide a general overview of the wine filière and conduct an analysis of the main actors, grape growers, co-operatives, wine brokers, wine merchants and clusters according to the research questions introduced previously.
Keywords: 330; Industrial organization; Market chain; Theoretical references; Wine industry